Crustal thinning in the northern Tyrrhenian Rift: Insights from multichannel and wide‐angle seismic data across the basin. Issue 3 (26th March 2014) - Moeller, S.; Grevemeyer, I.; Ranero, C. R.; Berndt, C.; Klaeschen, D.; Sallares, V.; Zitellini, N.; de, R.
Abstract Extension of the continental lithosphere leads to the formation of rift basins or rifted continental margins if breakup occurs. Seismic investigations have repeatedly shown that conjugate margins have asymmetric tectonic structures and different amount of extension and crustal thinning. Here we compare two coincident wide‐angle and multichannel seismic profiles across the northern Tyrrhenian rift system sampling crust that underwent different stages of extension from north to south and from the flanks to the basin center. Tomographic inversion reveals that the crust has thinned homogeneously from 24 km to 17 km between the Corsica Margin and the Latium Margin implying a β factor of 1.3–1.5. On the transect 80 km to the south, the crust thinned from 24 km beneath Sardinia to a maximum of 11 km in the eastern region near the Campania Margin (β factor of 2.2). The increased crustal thinning is accompanied by a zone of reduced velocities in the upper crust that expands progressively toward the southeast. We interpret that the velocity reduction is related to rock fracturing caused by a higher degree of brittle faulting, as observed on multichannel seismic images. Locally, basalt flows are imaged intruding sediment in this zone, and heat flow values locally exceed 100 mW/m2. Velocities within the entire crust range 4.0–6.7 km/s, which are typical for continental rocks and indicate that significant rift‐related magmatic underplating may not be present. The characteristics of the pre‐tectonic, syn‐tectonic and post‐tectonic sedimentary units allow us to infer the spatial and temporal evolution of active rifting. In the western part of the southern transect, thick postrift sediments were deposited in half grabens that are bounded by large fault blocks. Fault spacing and block size diminish to the east as crustal thinning increases. Recent tectonic activity is expressed by faults cutting the seafloor in the east, near the mainland of Italy. The two transects show the evolution from the less extended rift in the north with a fairly symmetric conjugate structure to the asymmetric margins farther south. This structural evolution is consistent with W‐E rift propagation and southward increasing extension rates.